(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Monodispersed platinum nanoparticles (Pt-NPs) with an average diameter dTEM 3.1±1.0 nm were synthesized by EtOH reduction method in the presence of an organic polymer poly (vinylpyrrolidone) (PVP) with an average molecular weight of 40,000. Using this particles as seed, size tunable Pt-NPs of dTEM 3.1±1.0 nm to 5.7±1.6 nm with sufficient monodispersity were synthesized by multiple step seeding growth. Formation of Pt-NPs was confirmed by the UV-visible absorption spectra. Transmission electron micrographs (TEM) and powder X-ray diffraction (XRD) patterns confirmed that the particles were single crystalline with fcc crystal geometry. Bangladesh J. Sci. Ind. Res. 50(2), 87-92, 2015